Cancer Stem Cells as a Potential Target to Overcome Multidrug Resistance - Cho, Yena; Kim, Yong Kee (Frontiers in Oncology, 2020)
Multidrug resistance (MDR), which is a significant impediment to the success of cancer chemotherapy, is attributable to various defensive mechanisms in cancer. Initially, overexpression of ATP-binding cassette (ABC) transporters such as P-glycoprotein (P-gp) was considered the most important mechanism for drug resistance; hence, many investigators for a long time focused on the development of specific ABC transporter inhibitors. However, to date their efforts have failed to develop a clinically applicable drug, leaving only a number of problems. The concept of cancer stem cells (CSCs) has provided new directions for both cancer and MDR research. MDR is known to be one of the most important features of CSCs and thus plays a crucial role in cancer recurrence and exacerbation. Therefore, in recent years, research targeting CSCs has been increasing rapidly in search of an effective cancer treatment. Here, we review the drugs that have been studied and developed to overcome MDR and CSCs, and discuss the limitations and future perspectives.